Experimentos de baixo custo para abordar concepções alternativas sobre corrente elétrica em circuitos simples - Lima, Francisco Cristiano Barbosa (2018)
We describe in this dissertation the planning, elaboration and application of an educational product aimed at the use of low-cost materials in the manufacture of simple electrical circuits intended to approach basic concepts of electricity in secondary education. The product was applied in a public school in the city of Itaiçaba, mesoregion of Jaguaribe, in the State of Ceará. From the answers presented in the pre-test and in the clinical interviews, we observed the recurrence of alternative conceptions long reported in the literature. We conclude that a pedagogical approach making concomitant use of clinical experiments and interviews may be potentially useful in overcoming alternative conceptions, with conceptual change. Throughout the whole teaching-learning process, the students' satisfaction was remarkable as they manipulated the circuits and visualized the solutions to the questions put to them as a pre-test. They demonstrated satisfaction because they proved something with equipment that they had built